The Beijing Consensus − Chinese development model - Tylec, Tomasz (Konsensus pekiński – chiński model rozwoju, 2019)
The article attempts to present the essence and main assumptions of the concept of China’s socio-economic policy in opposition to the concept of economic policy defined by the principles of Washington Consensus. The Beijing Consensus is a set of principles characterizing the economic policy implemented by the Communist Party of China since the late 1970s, resulting in the intensification of the country’s economic growth and development, while maintaining the specificity of the political system and taking into account China’s socio-economic conditions. China, recognizing that the country faces a unique set of challenges and therefore requires unique solutions, has chosen its own alternative development concept. The socio-economic policy implemented according to certain principles, meets not only social needs, but also becomes an increasingly noticeable way to implement Chinese soft power on the international stage. By making this choice, China remains on its own path of rapid development and unprecedented increase in political and economic significance in the global economy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 154-163
Keywords: China; Beijing Consensus; socio-economic policy; Chiny; konsensus pekiński; polityka społeczno-gospodarcza